Shotgun metagenomic sequencing of the first case of monkeypox virus in Brazil, 2022 - Claro, Ingra Morales (2022)
Monkeypox virus (MPXV), a zoonotic virus endemic to the African continent, has been reported in 33 non-endemic countries since May 2022. We report an almost complete genome of the first confirmed case of MPXV in Brazil. Shotgun metagenomic sequencing was completed in 18 hours, from DNA extraction to consensus sequence generation.